Acetylcholine release and choline uptake by cuttlefish (Sepia officinalis) optic lobe synaptosomes - Nunes, M. Alexandra (2018)
Acetylcholine (ACh), which is synthesized from choline (Ch), is believed to hold a central place in signaling mechanisms within the central nervous system (CNS) of cuttlefish (Sepia officinalis) and other coleoid cephalopods. Although the main elements required for cholinergic function have been identified in cephalopods, the transmembrane translocation events promoting the release of ACh and the uptake of Ch remain largely unsolved. The ACh release and Ch uptake were quantitatively studied through the use of in vitro chemiluminescence and isotopic methods on a subcellular fraction enriched in synaptic nerve endings (synaptosomes) isolated from cuttlefish optic lobe.